Experimental assessment of emissions maps of a single-cylinder compression ignition engine powered by diesel and palm oil biodiesel-diesel fuel blends. (June 2020) - Mejía, A.; Leiva, M.; Rincón-Montenegro, A.; Gonzalez-Quiroga, A.; Duarte-Forero, J.
Abstract: Diesel engines applications cover a broad spectrum, ranging from vehicles that transport passengers and move goods to specialized vehicles and equipment used in the construction and agriculture industries. However, diesel engines are a significant source of pollutant emissions that contribute to poor air quality, negative human health impacts, and climate change. This experimental case study develops emission maps based on statistical models for a single-cylinder, four-stroke, air-cooled diesel engine as a function of torque and engine speed. The tested fuels were 100% diesel (B0), and blends with 5% (B5) and 10% (B10) biodiesel originating from African oil palm ( Elaeis guineensis ). The study explores the individual contributions of NO and NO2 to NOx and discusses the correlation between CO and O2 emission maps. The statistical models of CO, CO2, and O2 feature R 2 adjusted values greater than 0.8, while the models of NO and NO2 show R 2 adjusted values of around 0.6. The apparent discrepancies in CO emission trends among previous studies are explained. The emission maps developed here are a practical alternative to predictive models and can assist in engine calibration and aftertreatment optimization while saving time and costs. Graphical abstract: Image 1